Superhydrophobic polypropylene/ethylene-propylene-diene terpolymer thermoplastic vulcanizates for continuous oil-water separation. (May 2023) - Shan, Xiu; Yang, Linji; Huang, Ping; Wang, Zhaobo
Although the construction of superwettability materials for oil-water separation has become a research hotspot, it is still a thorny issue due to its easy pollution to the environment during the preparation process. In this paper, we reported the functional PP/EPDM TPV film (with a contact angle of oil and water is 0° and 157.9±2.9°) as superhydrophobic and superoleophilic materials with reproducible processing characteristics at high temperature; moreover, during the molding process the etched aluminum foil was used as a template for the preparation of functional TPV film which was used in the efficient separation treatment of oily wastewater. It should be noted that a novel method was proposed for the continuous oil-water separation via a pressure response through valve, which was different from the traditional gravity-driven method and the permeable oil-water separation. The flexible PP/EPDM TPV film was rolled up and loaded into the through valve and the gap between films was used as the pressure response channel of oil-water separation. The novel functional TPV film used in the continuous oil-water separation was recyclable, environmentally friendly, and easy to industrialize, indicating the great potential in practical applications.